STUDI GEOKIMIA FLUIDA PANASBUMI DAERAH PROSPEK PANASBUMI NGLIMUT, G. UNGARAN KECAMATAN LIMBANGAN, KABUPATEN KENDAL JAWA TENGAH - Brahmo Emianto, Yohanes; Aribowo, Yoga (TEKNIK, 2011)
Fluid geochemistry is a useful method to analyse lateral and vertical processes and trends in a geothermalsystem, just like a blood and urine analysis to determine the functions of internal organs in human body. Fluidsgeochemistry study in Nglimut Geothermal Prospect has conducted to get information about type andcharacteristics of fluids, to predict reservoir temperature, and sub surface hidrogeochemical cycle model.From fluids geochemistry analysis, the most significant constituent is HCO3, and thus all fluids classified intobicarbonate water. Based on gethermometry analysis, the average reservoir temperature calculated is about206oC and classified into high enthalpy system